A Baker’s Dozen of Top Antimicrobial Stewardship Intervention Publications in 2017 - Chastain, Daniel B (Open Forum Infect Dis, 2019)
With an increasing number of antimicrobial stewardship–related articles published each year, attempting to stay current is challenging. The Southeastern Research Group Endeavor (SERGE-45) identified antimicrobial stewardship-related peer-reviewed literature that detailed an “actionable” intervention for 2017. The top 13 publications were selected using a modified Delphi technique. These manuscripts were reviewed to highlight the “actionable” intervention used by antimicrobial stewardship programs to provide key stewardship literature for training and teaching and identify potential intervention opportunities within their institutions.